Effect of farmyard manure, organic manure and balanced fertilizers application on the productivity and soil fertility in pearl millet (Pennisetum glaucum)- mustard (Brassica juncea) cropping sequence in sandy loam soil of semi-arid regions - KUMAR, ANIL; CHUGH, L K; YADAV, DEV VART; MALIK, R S; KUMAR, L C MANOJ (The Indian Journal of Agricultural Sciences, 2016)
The experiment was conducted at the research farm of Department of Genetics and Plant Breeding, CCS Haryana Agricultural University, Hisar from 2007-08 to 2009-10 to study the effect of farmyard manure and balanced fertilizers on production potential, economic viability and soil properties in the pearl millet [Pennisetum glaucum (L) R. Br.]- mustard [Brassica juncea (L.) Czernj. and Coss.] cropping sequence. The study consisted of 12 treatment combinations of farmyard manure and inorganic fertilizers with micronutrients were laid out in Factorial Randomized Block Design with three replications. The mean data revealed that use of balanced fertilizers (Potash, gypsum, ZnSO4 and FeSO4) along with application of 5.0 tonnes FYM/ha in pearl millet-mustard crop sequence produced 7.5 per cent higher pearl millet grain yield (3.59 tonnes/ha) and 8.2 per cent more mustard seed yield (1.96 tonnes/ha) than no FYM application (3.34 tonnes/ha by pearl millet and 1.81 tonnes/ha by mustard). Among different balanced nutrient treatments; recommended dose of nitrogen and phosphorous for both the crops, i.e. 120 kg N + 60 kg P/ha for pearl millet and 80 kg N + 30 kg P/ha for mustard along with 5.0 tonnes FYM/ha + 20 kg K2O/ha + 200 kg gypsum +10 kg ZnSO4 /ha + 10 kg FeSO4/ha (F5) produced maximum pearl millet grain yield (3.91 tonnes/ha) and mustard seed yield (2.31 t/ha), pearl millet equivalent yield (11.91 t/ha) and gross returns (Rupees93 051/ha) whereas, maximum net returns (RUPEES 44 529 /ha) and B:C ratio (1:93) were observed in the treatment 5.0 t FYM /ha + RD of N and P +20 kg K2O/ha + 200 kg gypsum/ha + 10 kg ZnS04 kg/ha (F4). The F5 treatment decreased pH (7.8) and EC (0.33 ds/m), improved the organic carbon (0.37%), available N (205 kg/ha), P2O5 (17.7 kg/ha), K2O (331 kg/ha), Fe (3.48 ppm), Zn (2.30 ppm) and S (4.30 ppm) status in comparison to values of 8.0 and 0.36. ds/m 0.34%, 196 kg/ha, 17.3 kg/ha, 323.7 kg/ha, 3.36 ppm, 2.15 ppm and 4.45 ppm, respectively in RD of N and P + 20 kg K2O/ha + 200 kg gypsum/ha + 10 kg ZnSO4/ha + 10 kg FeSO4/ha treatment when no FYM was used. The quality traits; protein content in pearl millet, oil content and oil yield were also found superior in the F5 treament than all other combinations of balanced fertilizers with and without 5.0 tonnes FYM/ha.